Beyond Harms and Benefits: Rethinking Duties to Disclose Misattributed Parentage - Garrett, Jeremy R. (The Hastings Center report, 2015)
In this issue of the Hastings Center Report, Amulya Mandava, Joseph Millum, and Benjamin E. Berkman revisit an old conundrum—whether to disclose incidental findings of misattributed parentage—in light of new developments in genomic sequencing that will make that conundrum both more complex and more common. While the authors’ defense of nondisclosure as the appropriate default action in genomic research aligns with prior thinking and practice, their exploration of philosophical foundations is refreshingly rigorous and developed. The final product of their analysis—an applied taxonomy of the types of harms and benefits that can result from disclosure of misattributed parentage—is an important contribution to the literature on this subject and worthy of serious consideration by genomic researchers and bioethicists alike. Despite these virtues, I am struck by the authors’ deference to the traditional assumption that disclosure ethics can be adequately understood and appreciated within a purely consequentialist framework.